Glycobiology Aspects of the Periodontal Pathogen Tannerella forsythia - Christina Schäffer; Andrea Koerdt; Paul Messner; Zoë A. Megson; Valentin Friedrich; Gerhard Sekot; Gerald Posch (Biomolecules, 2012)
Glycobiology is important for the periodontal pathogen Tannerella forsythia, affecting the bacterium’s cellular integrity, its life-style, and virulence potential. The bacterium possesses a unique Gram-negative cell envelope with a glycosylated surface (S-) layer as outermost decoration that is proposed to be anchored via a rough lipopolysaccharide. The S-layer glycan has the structure 4‑MeO-b-ManpNAcCONH2-(1→3)-[Pse5Am7Gc-(2→4)-]-b-ManpNAcA-(1→4)-[4-MeO-a-Galp-(1→2)-]-a-Fucp-(1→4)-[-a-Xylp-(1→3)-]-b-GlcpA-(1→3)-[-b-Digp-(1→2)-]-a-Galp and is linked to distinct serine and threonine residues within the D(S/T)(A/I/L/M/T/V) amino acid motif. Also several other Tannerella proteins are modified with the S‑layer oligosaccharide, indicating the presence of a general O‑glycosylation system. Protein O‑glycosylation impacts the life-style of T. forsythia since truncated S-layer glycans present in a defined mutant favor biofilm formation. While the S‑layer has also been shown to be a virulence factor and to delay the bacterium's recognition by the innate immune system of the host, the contribution of glycosylation to modulating host immunity is currently unraveling. Recently, it was shown that Tannerella surface glycosylation has a role in restraining the Th17-mediated neutrophil infiltration in the gingival tissues. Related to its asaccharolytic physiology, T. forsythia expresses a robust enzymatic repertoire, including several glycosidases, such as sialidases, which are linked to specific growth requirements and are involved in triggering host tissue destruction. This review compiles the current knowledge on the glycobiology of T. forsythia.